2017
DOI: 10.1364/ao.56.00d115
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 3D imaging of the human tympanic membrane using a wide-field diagonal-scanning optical coherence tomography probe

Abstract: A wide-field optical coherence tomography (OCT) probe was developed that adapts a diagonal-scanning scheme for three-dimensional (3D) in vivo imaging of the human tympanic membrane. The probe consists of a relay lens to enhance the lateral scanning range up to 7 mm. Motion artifacts that occur with the use of handheld probes were found to be decreased owing to the diagonal-scanning pattern, which crosses the center of the sample to facilitate entire 3D scans. 3D images could be constructed from a small number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…However, the acquisition of OCT visualizations of in vivo normal regions was a challenging task using the employed OCT system configuration. Since the OCT assessments of the current study clearly revealed the biofilm growth due to disease with a structural comparison between healthy homogenous structure and infected heterogeneous structure through structural abnormalities (with a biofilm growth), the comparison between healthy and infected were conducted using the obtained raw ex vivo OCT visualizations, while supportive literature reports emphasizing healthy in vivo structures of the examined regions, which were acquired using handheld-OCT and surgical-OCT maneuvers can be referred elsewhere [26], [29], [35]- [38]. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the acquisition of OCT visualizations of in vivo normal regions was a challenging task using the employed OCT system configuration. Since the OCT assessments of the current study clearly revealed the biofilm growth due to disease with a structural comparison between healthy homogenous structure and infected heterogeneous structure through structural abnormalities (with a biofilm growth), the comparison between healthy and infected were conducted using the obtained raw ex vivo OCT visualizations, while supportive literature reports emphasizing healthy in vivo structures of the examined regions, which were acquired using handheld-OCT and surgical-OCT maneuvers can be referred elsewhere [26], [29], [35]- [38]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution video and color images of the examined mastoid mucosa and TM regions were acquired using a miniaturized commercially available high-resolution optical microscope integrated charge-coupled device video camera with 1.3 megapixels. The system processing methods and the detailed configurations of the OCT instrumentation used were described previously [28], [29].…”
Section: Optical Inspection System Configurationmentioning
confidence: 99%
“…In this case, the field-of-view for OCT is limited to a few millimeters and is not sufficient for scanning the entire tympanic membrane. MacDougall et al 17 and Park et al 23 presented optical solutions reaching an extended fieldof-view up to 7 mm. 23 An alternative approach for examining the middle ear is endoscopic OCT, 13,24 realized with gradientindex (GRIN) optics providing a field-of-view up to 4 mm for imaging middle ear structures in mice 13 or up to 10 mm for imaging human tympanic membranes.…”
Section: Introductionmentioning
confidence: 99%
“…MacDougall et al 17 and Park et al 23 presented optical solutions reaching an extended fieldof-view up to 7 mm. 23 An alternative approach for examining the middle ear is endoscopic OCT, 13,24 realized with gradientindex (GRIN) optics providing a field-of-view up to 4 mm for imaging middle ear structures in mice 13 or up to 10 mm for imaging human tympanic membranes. 24 Endoscopic OCT can facilitate in vivo imaging, because the curved auditory canal is less impairing and the wide field-ofview allows the assessment of nearly the entire tympanic membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Some approaches endeavor to improve the performance and image quality of 3D imaging display, such as the experimental demonstration to perform an extended depth of field (DOF) in integral 3D imaging using a single large aperture liquid crystal lens or applying the gradient amplitude modulating method for the DOF enhancement . With this intention, there is great potential to explore this method to increase the resolution of a 3D image reconstruction, the use of normalized computational technique, optical modulation method, photon counting 3D imaging technique, and the optical coherence tomography technique for structural investigation have been acquiring increasing relevance to medical and biological applications. Furthermore, these imaging techniques have been primarily associated with the holographic display, which is a type of display that utilizes light diffraction to create a virtual 3D image of an object, has been rapidly popularized in recent years.…”
Section: Introductionmentioning
confidence: 99%